The Future of the Superintendency: Women Leaders Who Choose to Leave - Marilyn Tallerico; Joan N. Burstyn (Educational Considerations, 1995)
These women were open to entertaining the possibilities of exercising influence and making expert contributions in roles other than "at the top" of the structural hierarchy.